Stellate ganglion blockade under ultrasound-guidance and the physiological responses in the rat - Tran, Robert M. N.; Malik, Shaista; Reist, Christopher; Oh, Chad K.; Abdul-Musawir, Najeebah; Tjen-A-Looi, Stephanie C.; Fu, Liang-Wu; Baird, Theodore J.; Nguyen, Anh T.; Gong, Yiwei D.; Guo, Zhi-Ling (Frontiers in Physiology, 2025)
Stellate ganglion blockade (SGB) is a practical approach to managing many clinical disorders. Ultrasound-guided SGB is currently adopted as a more effective and safer method in humans. Developing this technique in rats would facilitate further study of SGB application. The present study examined physiological responses following ultrasound-guided SGB in Sprague-Dawley rats. Under general anesthesia, lidocaine containing Chicago blue dye (1.0%–1.5% in 40–60 µL) was injected into the unilateral stellate ganglion (SG). Ptosis was observed on the ipsilateral right (n = 8) or left (n = 7) side of lidocaine administration. No ptosis was noted in any controls by 0.9% normal saline injection into the right (n = 6) or left (n = 6) SG. Heart rate (HR) was significantly decreased after administration of lidocaine (344 ± 32 to 289 ± 47 bpm; p = 0.015, pre-vs. after-injection), but not after normal saline, into the right SG. HR was unaltered after injecting lidocaine or normal saline into the left SG. Heart rate variability analysis showed that SGB with lidocaine on the right or left side caused a decrease in the ratio of the power of low-frequency over high-frequency. Respiratory rate, body temperature, and general conditions were unchanged in all rats, regardless of left or right SGB. Chicago blue dye was confirmed to be distributed in the SG region. No bleeding or tissue damage was evident in the injected SG area. Our findings suggest that ultrasound-guided unilateral SGB effectively inhibits cervicothoracic sympathetic nerves in rats and enhances heart rate variability, and sympathetic nerves controlling HR are likely predominantly associated with the right SG in the rat.